Pentahelix Collaboration in the Sainvisma Program in the Development of Impactful and Sustainable MSMEs - Ahmad Ramdhani; Ali Irfan (International Journal of Multidisciplinary Sciences and Arts, 2026)
This study discusses pentahelix collaboration as a project-based learning innovation (PjBL) of the visual communication design study program (DKV) of the Harapan Bersama Polytechnic in the Sainvisma (Brand Visual Design) program which is carried out in the third semester integrated with five courses, namely Advertising, Computer Graphics 3, Cinematography 1, Audio Visual and 3D Animation. The Sainvisma program in collaboration with MSMEs fostered by the Tegal SOE House brings together DKV students as a Content Creator team with actors MSMEs were selected to collaborate on pentahelix which consists of five elements of ABCGM, namely Academy, Business, Community, Government and Media with the aim of providing MSME assistance through the creation of MSME profiles and short videos of commercial advertisements for superior products for the needs of Instagram and TikTok social media promotion. This research method uses qualitative descriptive which focuses on the objects raised to solve existing problems. The stages of implementing the Project-Based Learning (PjBL) method are carried out by providing student knowledge and skills, project preparation, project implementation and exposure of project results. The results of pentahelix collaboration are the main key to synergy between elements to develop learning innovations that transform into benefits for MSMEs, improve the quality of learning and the quality of students in the link and match of the OBE-based curriculum (Outcame Based Education). As well as supporting the realization of the Sustainable Development Goals (SDGs), one of which is in achieving the acceleration of economic development and improving the community environment.